Understanding Tolerance to Biocides and its Consequences in Clinical Isolates of Klebsiella pneumoniae - How to Treat an ESKAPE Pathogen - Ryder, Stephen (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2024)
Biocides such as Triclosan, Benzalkonium Chloride, and Chlorhexidine have been used as disinfectants for many years, however the effects of their use and the subsequent selective pressures applied to microbial populations are still uncertain. This thesis investigates the phenotypic consequences of adaptation by clinical isolates of Klebsiella pneumoniae to sub-inhibitory concentrations of these biocides.
APPROVED
Keywords: Biocides; Klebsiella pneumoniae; Triclosan; Benzalkonium chloride; Chlorhexidine; Antibiotic resistance